Civic Skills Mastery as a Widow's Strategy In Fulfilling Life's Needs: a Legal and Social Justice Analysis - Mazid, Sukron; Wulansari, Atsani; Setyorini, Ika (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2024)
This study aims to examine how the mastery of civic skills by widows can help them in making ends meet, from a legal and social justice perspective. Widows often face considerable social and economic challenges in making ends meet. Mastery of civic skills such as knowledge of legal rights, social engagement, and participation in public decision-making can be applied to overcome these challenges. This research uses a descriptive qualitative approach through observation, in-depth interview and documentation techniques with a number of widows in Magelang urban area. The results showed that understanding of legal rights as well as the ability to participate in community significantly helps widows overcome the social and economic challenges they face. The legal system can improve the position of widows through proactive policies that support social justice.